KONSEPSI HALAL DALAM BERNEGARA - Ahmad Saupi, Ahmad Saupi (An Nawawi, 2022)
This study aims to determine the concept of halal in the state. Halal is an important activity for Muslims in religion. Marking the obedience of a Muslim in carrying out his worship. The basic concept of halal in the state is very important to become the understanding of citizens, in order to support the halal succession, it can be applied to broader aspects for the good of the Indonesian nation into the future. This study uses a qualitative method that is a library research. This type of data and research materials comes from primary and secondary data. The primary source used is Law Number 33 of 2014 concerning Halal Product Guarantee, and secondary sources in this study are supporting references about halal. The data collection method is in the form of library data that has been selected, searched, presented and analyzed. The data analysis technique is in the form of content analysis, so that the meaning and relationship of halal in the state can be known The results of this study reveal that the meaning and relationship of halal in the state based on Law Number 33 of 2014 concerning Halal Product Guarantee, places the position of halal in a limited sense, namely as a predicate attached to the object, the object is a halal product. Meanwhile, the law does not regulate halal as a norm, namely halal which has provisions regulating human behavior.